La naissance de la justice en débat : représentations contemporaines du procès d’Oreste - Claire Lechevalier (Criminocorpus)
Aeschylus’ Oresteia, staging the trial of Orestes by a popular court and ending with his acquittal, appears in modern times as the origin both of the theatre and of justice and democracy, after the reign of revenge. Yet to contemporary directors, representing what is traditionally interpreted as a happy ending, and the notion of the city’s miraculously obtained cohesion (through the intercession of Athena), raise a good many doubts and questions. Is it still possible now to adhere to the representation of a utopian, miraculously responsible democracy, but also to the very longing for justice, in a world that, after the radical fracture of Auschwitz, has gone through the upheavals that followed it? Is it still possible to represent a well-ordered world, or a civic, political and theological unit, in a universe that is reputedly split up, without moorings? The comparative analysis of French and German versions of the trial of Orestes shows how radically at variance these two interpretative traditions are.